2023
DOI: 10.3390/healthcare11020277
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Saudi Society’s Knowledge Regarding Hypothyroidism and Its Neuropsychiatric Clinical Manifestations

Abstract: Background: This study was conducted to assess the level of knowledge and awareness of hypothyroidism and its neuropsychiatric clinical manifestations among the Saudi population. Methods: This was a cross-sectional study employing a convenient sampling technique, conducted between February and May 2022. A questionnaire was distributed online to all participants in all five regions. Results: In this survey, a total of 2016 Saudi citizens participated. When asked about depression, more than half of the participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
1
1
1
Order By: Relevance
“…Gender was found to be significantly associated with the level of knowledge about thyroid disorders with the female gender tending to have higher levels of knowledge compared to males, and this was found to be consistent with the findings in Alzahrani et al's study [ 5 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Gender was found to be significantly associated with the level of knowledge about thyroid disorders with the female gender tending to have higher levels of knowledge compared to males, and this was found to be consistent with the findings in Alzahrani et al's study [ 5 ].…”
Section: Discussionsupporting
confidence: 89%
“…The proposed research project aimed to investigate the level of public awareness and knowledge of thyroid disease, identify the factors that influence thyroid disease recognition and treatment, and develop effective strategies to improve public awareness of thyroid disease. The findings from this study can inform the development of effective educational programs to improve early detection and treatment of thyroid disease, ultimately improving health outcomes for the population in the Tabuk region [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, only 25% of patients had a high level of knowledge, while the majority had a moderate (41%) to poor level of knowledge (34%). This contrasts with a study from Saudi Arabia in 2023, where only 9% of participants had a high level of knowledge, while the remaining 91% had a low level of understanding [ 35 ]. Other research in Saudi Arabia indicated that half of the respondents had a moderate knowledge level [ 36 ], but only 14.2% showed a satisfactory understanding of the condition [ 37 ].…”
Section: Discussioncontrasting
confidence: 57%